H19 lncRNA Promotes Skeletal Muscle Insulin Sensitivity in Part by Targeting AMPK - Geng, Tingting; Liu, Ya; Xu, Yetao; Jiang, Ying; Zhang, Na; Wang, Zhangsheng; Carmichael, Gordon G.; Taylor, Hugh S.; Li, Da; Huang, Yingqun (Diabetes (New York, N.Y.), 2018)
Skeletal muscle plays a pivotal role in regulating systemic glucose homeostasis in part through the conserved cellular energy sensor AMPK. AMPK activation increases glucose uptake, lipid oxidation, and mitochondrial biogenesis, leading to enhanced muscle insulin sensitivity and whole-body energy metabolism. Here we show that the muscle-enriched H19 long noncoding RNA (lncRNA) acts to enhance muscle insulin sensitivity, at least in part, by activating AMPK. We identify the atypical dual-specificity phosphatase DUSP27/DUPD1 as a potentially important downstream effector of H19. We show that DUSP27, which is highly expressed in muscle with previously unknown physiological function, interacts with and activates AMPK in muscle cells. Consistent with decreased H19 expression in the muscle of insulin-resistant human subjects and rodents, mice with genetic H19 ablation exhibit muscle insulin resistance. Furthermore, a high-fat diet downregulates muscle H19 via both posttranscriptional and epigenetic mechanisms. Our results uncover an evolutionarily conserved, highly expressed lncRNA as an important regulator of muscle insulin sensitivity.